ANALISIS KINERJA KEPEMIMPINAN ORGANISATIONAL DI PT MULTI INDOMANDIRI - Devina Delta Maharan; Uus MD Fadli (JOURNAL SAINS STUDENT RESEARCH, 2024)
PT Multi Indomandiri is one of the leading global companies operating in the consumer products manufacturing and distribution sector. With a diverse product range and extensive distribution network, PT Multi Indomandiri has become a major player in the consumer goods industry in the Southeast Asia region. The company has been operating since 2013, and has experienced ups and downs in performance that are affected by a number of internal and external variables, including organizational leadership which is an important element in determining the company's success. Data collection was conducted through qualitative methods, semi-structured interviews with several employees from various levels of positions to obtain more in-depth information about their perspectives and experiences related to organizational leadership performance. This research is expected to contribute to improving organizational leadership performance at PT Multi Indomandiri and other companies. By implementing in this research, it is expected that PT Multi Indomandiri can improve employee performance, increase company productivity, and achieve its business goals more effectively.